"Taylorism" before Taylor: the agricultural work in Columela (1st century AD) - Rocha, Ivan Esperança (Revista Archai, 2019)
Taylorism is identified with Frederick Winslow Taylor’s system of organizing and managing the work proposed at the beginning of the twentieth century, and seeks to achieve maximum production and yield with the minimum of time and effort expended, through standardization and simplifications at a time of industry expansion that required major concerns about work efficiency. Although initially tied to industrial activity, taylorism was adapted to rationalize the most diverse economic activities, including agriculture. In this text the work De re rustica de Columela will be analyzed as a proposal of an “ancient taylorist” rationalization of work in a Roman villa of the 1st century BC, marked by processes of standardization and organization of the rural work.